Shifting Energy Based Optimization for All-Electric Vehicle Equipped with Electric-Mechanical Continuously Variable Transmission - Ye, Ming; Ren, Hong (Recent Patents on Mechanical Engineering, 2015)
The electric-mechanical continuously variable transmission which is driven by electric motor is a perfect type of transmission for electric vehicle. In this paper, the first objective is to address recent patents on the configuration of electric-mechanical continuously variable transmission. The second objective is optimization of the energy consumption of all-electric vehicle equipped with electric- mechanical continuously variable transmission. Global optimization of electric vehicle equipped with EMCVT running in New European Driving Cycle has been carried out based on dynamic programming. In this optimization state of charge and transmission ratio these are state variable and decision variable, respectively. Ratio shifting model was built to estimate energy consumption during shifting. New optimal control strategies were achieved by taking shifting energy consumption as cost function. Test results show that shift times and energy consumed are both reduced with this control strategy. Recent patents on the configuration of electric-mechanical continuously variable transmission are also addressed.
Keywords: transmission ratios control